2014
DOI: 10.1371/journal.pone.0114908
|View full text |Cite|
|
Sign up to set email alerts
|

Tetrahydrocurcumin Protects against Cadmium-Induced Hypertension, Raised Arterial Stiffness and Vascular Remodeling in Mice

Abstract: BackgroundCadmium (Cd) is a nonessential heavy metal, causing oxidative damage to various tissues and associated with hypertension. Tetrahydrocurcumin (THU), a major metabolite of curcumin, has been demonstrated to be an antioxidant, anti-diabetic, anti-hypertensive and anti-inflammatory agent. In this study, we investigated the protective effect of THU against Cd-induced hypertension, raised arterial stiffness and vascular remodeling in mice.MethodsMale ICR mice received CdCl2 (100 mg/l) via drinking water fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 60 publications
(80 reference statements)
1
35
0
Order By: Relevance
“…Also reported in the study was the crosslinking of myofibrillar collagen fibers forming an irregular branching pattern and complicated matrix network [90]. In addition to the cardiac tissues, Cd alters the aorta's histological integrity as evidenced by the induction of hypertrophic aortic wall remodeling by hyperplasia of smooth muscle cells, increased collagen deposition, decreased elastin and increased aortic medial wall matrix metalloproteinases [91]. Another study evaluating the histopathological changes in the heart of male albino rats treated with 200 mg/L Cd for 8 weeks reported focal hyaline degeneration and perivascular fibrosis with narrowed lumen of cardiac blood vessels after 4 weeks, hyaline degeneration with focal areas of coagulative necrosis and interstitial fibrosis in the left ventricle after 8 weeks [92].…”
Section: Cadmium-induced Tissue Injurymentioning
confidence: 96%
“…Also reported in the study was the crosslinking of myofibrillar collagen fibers forming an irregular branching pattern and complicated matrix network [90]. In addition to the cardiac tissues, Cd alters the aorta's histological integrity as evidenced by the induction of hypertrophic aortic wall remodeling by hyperplasia of smooth muscle cells, increased collagen deposition, decreased elastin and increased aortic medial wall matrix metalloproteinases [91]. Another study evaluating the histopathological changes in the heart of male albino rats treated with 200 mg/L Cd for 8 weeks reported focal hyaline degeneration and perivascular fibrosis with narrowed lumen of cardiac blood vessels after 4 weeks, hyaline degeneration with focal areas of coagulative necrosis and interstitial fibrosis in the left ventricle after 8 weeks [92].…”
Section: Cadmium-induced Tissue Injurymentioning
confidence: 96%
“…In vitro experiments on endothelial cells have shown that Cd concentrations at low doses, below the currently considered toxic level, lead to increased cell permeability due to cell death (Messner et al 2009;PĂ©rez DĂ­az et al 2013). Sangartit et al (2014) reported the thickening and stiffening of the aortic wall in Cd-exposed mice which were associated with alterations in the vascular composition. Similar outcomes are also reflected in the current study suggesting altered mechanical forces during exposure to Cd that may be triggered by adaptive restructuring of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…We proposed that Cd content in the aorta might induce aortic weakening through the adverse effects on smooth muscle cell metabolism and the attenuation of vascular reactivity to vasoactive agents. A combination of these effects results from long-term damage of endothelial and vascular smooth muscle cells caused by Cd intoxication Sangartit et al 2014). We also found that Cd promotes vascular smooth muscle growth and proliferation, enhances vascular remodeling, and increases arterial stiffening ).…”
Section: Cadmium-induced Cardiovascular Dysfunctionmentioning
confidence: 99%